Case Report: Novel Heterozygous DFNA5 Splicing Variant Responsible for Autosomal Dominant Non-syndromic Hearing Loss in a Chinese Family - Chen, Xi; Jia, Bao-Long; Li, Mei-Hui; Lyu, Yuan; Liu, Cai-Xia (Frontiers in Genetics, 2020)
Autosomal dominant non-syndromic hearing loss (ADNSHL) has a broad phenotypic spectrum which includes bilateral, symmetrical, and high-frequency sensorineural hearing loss, that eventually progresses into hearing loss at all frequencies. Several genetic variations have been identified as causal factors underlying deafness, autosomal dominant 5 (DFNA5) gene-related hearing loss. Here, we report a novel mutation (c.991-1G>C) in DFNA5, which co-segregated with late-onset ADNSHL in a Chinese family and was identified via exome sequencing and Sanger sequencing of DNA from peripheral blood of the family members. Further sequencing of cDNA derived from peripheral blood mRNA revealed that the c.991-1G>C mutation led to the skipping of exon 8, which is a known pathogenic mechanism for DFNA5-related hearing loss.